2022
DOI: 10.3390/medicina58111658
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Nrf2 and HO-1 with the Severity of COVID-19 Disease

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) have significant roles in the development of a hyperinflammatory state in infectious diseases. We aimed to investigate the association of the serum concentrations of Nrf2 and HO-1 with the severity of COVID-19 disease. The study included 40 subjects with mild and moderately severe forms of the disease (MEWS scoring system ≤2). Twenty of the subjects had MEWS scores of 3 or 4, which indicate a severe form of the disease, and twenty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The presence of complications such as bacteriemia and sepsis can inhibit Nrf2 activation [47][48][49]. This is in line with research conducted on patients with COVID-19 infection [50][51][52] in which patients with the most severe form of the disease have lower Nrf2 values. When analyzing other exogenous activators of Nrf2, 1,25-dihydroxy vitamin D should be pointed out in COVID-19 infection.…”
Section: Clinical Implications Of Nrf2/ho-1 Pathway In Covid-19 Infec...supporting
confidence: 75%
“…The presence of complications such as bacteriemia and sepsis can inhibit Nrf2 activation [47][48][49]. This is in line with research conducted on patients with COVID-19 infection [50][51][52] in which patients with the most severe form of the disease have lower Nrf2 values. When analyzing other exogenous activators of Nrf2, 1,25-dihydroxy vitamin D should be pointed out in COVID-19 infection.…”
Section: Clinical Implications Of Nrf2/ho-1 Pathway In Covid-19 Infec...supporting
confidence: 75%
“…Nrf2/HO-1 has been reported to play a critical mediator in regulating antioxidative and antiviral immune response ( Loboda et al., 2016 ; Ma et al., 2024 ). Previous studies have shown that Rutin via Nrf2/HO-1signaling pathway relieve oxidative stress ( Mihic et al., 2022 ; Wu et al., 2023 ; Lee et al., 2024 ). In typical physiological conditions, the Nrf2 is primarily located within the cellular cytoplasm and forms a complex with its inhibitory partner, Kelch-like ECH-associated protein 1 (Keap1) ( Bellezza et al., 2018 ; Abdul-Muneer, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, pharmacologic activation of Nrf2 reduces activation of microglia and neuroinflammation, alleviates neurotoxicity, and improves synaptic and mitochondrial function in animals following lipopolysaccharide challenge [ 32 , 33 ]. Recent studies have shown that levels of Nrf2 and its antioxidant target genes in the plasma and tissues are significantly lower in COVID-19 patients than control subjects and that a lower levels of Nrf2 are negatively correlated with the levels of proinflammatory markers [ 23 , 34 , 35 ]. In the present study, we found that mRNA expression of Nrf2 was decreased in the PVN 1 week after completion of S1 protein injection and remained significantly lower 3 weeks later.…”
Section: Discussionmentioning
confidence: 99%